One-Year Audiologic Monitoring of Individuals Exposed to the 1995 Oklahoma City Bombing - Van Campen, Luann E.; Dennis, J. Michael; Hanlin, Renee C. R.; King, Sandra B.; Velderman, Amy M. (Journal of the American Academy of Audiology, 1999)
This longitudinal study evaluated subjective, behavioral, and objective auditory function in 83 explosion survivors. Subjects were evaluated quarterly for 1 year with conventional pure-tone and extended high-frequencies audiometry, otoscopic inspections, immittance and speech audiometry, and questionnaires. There was no obvious relationship between subject location and symptoms or test results. Tinnitus, distorted hearing, loudness sensitivity, and otalgia were common symptoms. On average, 76 percent of subjects had predominantly sensorineural hearing loss at one or more frequencies. Twenty-four percent of subjects required amplification. Extended high frequencies showed evidence of acoustic trauma even when conventional frequencies fell within the normal range. Males had significantly poorer responses than females across frequencies. Auditory status of the group was significantly compromised and unchanged at the end of 1–year postblast.Abbreviations: ANOVA= analysis of variance, CF = conventional frequencies (0.25–8 kHz), EHF = extended high frequencies (10–20 kHz), LSD = least significant difference, psi = air pressure measured in pounds per square inch, dB pSPL = decibel re: peak sound pressure level, Q = quarterly evaluations, TNT = trinitrotoluene
Keywords: Acoustic trauma; auditory blast injury; extended high frequencies; noise-induced hearing loss; tinnitus